(untitled) (International Journal of Engineering and Computer Science, 2017)
Asymmetric key algorithms use different keys for encryption and decryption. The encryption key is public, decryption key is secret. Anyone can encrypt a message but only the one who knows the corresponding private key can decrypt it. This paper discuss asymmetric key algorithms with its advantages and disadvantages.